Analysis of Psychological Well-Being in High Grade Elementary School Children - Wita, I Wayan; Suarni, Ni Ketut; Margunayasa, I Gede (Journal La Medihealtico, 2023)
This research outlines an analysis of Psychological Well-Being in children who are in the final stages of primary school. The study used a literature review method with the aim of investigating and analysing a deeper understanding of aspects of psychological well-being in children of this age. Through analysing a number of literature sources, this study identified key factors that play a role in influencing psychological well-being in children in the late primary grades. These factors include, but are not limited to, social interactions at school, social support from family and peers, emotional development, adjustment skills and a supportive learning environment. The results of the analyzes suggest that psychological well-being in high school children is closely related to various psychosocial and environmental factors. Moreover, a better understanding of the relationship between these aspects and children's psychological well-being can provide valuable insights for educators, parents and mental health professionals in developing appropriate strategies and interventions to support positive psychological development in children at the primary school level. In conclusion, this study highlights the importance of a holistic understanding of the factors that influence psychological well-being in children in the upper primary grades. The implications of this study are expected to provide a foundation for the development of educational approaches and interventions aimed at improving the psychological well-being of children at this level.